2012
DOI: 10.3851/imp2084
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Virological Suppression: The Role of Adherence in the Late Haart Era

Abstract: HAART has increased the life expectancy of HIV-infected individuals significantly. Optimal adherence to HAART results in viral suppression and immune recovery in the majority of HIV-infected persons. Data from the early HAART era suggest that adherence levels of greater than 95% are necessary to achieve and maintain virological suppression. However, the optimal threshold of adherence required to maximize the pharmacological benefits of contemporary antiretroviral regimens, particularly in the virologically sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 57 publications
1
26
0
Order By: Relevance
“…However, HIV management also encompasses other considerations such as viral reservoirs, the effects of other inflammatory markers, and some evidence that suggests suboptimal adherence is associated with increased mortality. 18,19 Because of these reasons, in addition to the inherent complexity of medication adherence, the goalpost for ARV adherence should remain 100%.…”
Section: Discussionmentioning
confidence: 99%
“…However, HIV management also encompasses other considerations such as viral reservoirs, the effects of other inflammatory markers, and some evidence that suggests suboptimal adherence is associated with increased mortality. 18,19 Because of these reasons, in addition to the inherent complexity of medication adherence, the goalpost for ARV adherence should remain 100%.…”
Section: Discussionmentioning
confidence: 99%
“…The choice of adherence cutoff was based on previous studies and the expected adherence distribution. [30]…”
Section: Methodsmentioning
confidence: 99%
“…Of those who were non-adherent to their medication, 80% had experienced a relapse [29] care model was used and the study was conducted under routine outpatient circumstances. Other studies have shown that the medication compliance rate for non-psychiatric illness is 76%, while that for psychiatric illness is 58% [31].…”
Section: Discussionmentioning
confidence: 99%
“…Other structural barriers to maintaining engaged in care included distance from the clinic, confusion regarding their follow-up date, shame due to lack of follow-up, and conflict with work or school schedule. Interestingly, reasons cited for defaulting treatment in other studies of mentally ill patients have focused more on intolerance of side effects, relationship issues, and poor insight into their illness [30] [31].…”
Section: Discussionmentioning
confidence: 99%